Evaluation of a double skin façade performance: results from summer and winter monitoring - Marques da Silva, F. (2017)
Double Skin Façades are characterized by having at least two membranes between the interior occupied space and the exterior environment, separated by an air gap. They are becoming a possible solution to design new and retrofitted aesthetic buildings, with a great visual connection to the outside. They also allow for the possibility of using natural ventilation techniques on buildings, even when subjected to great external noise and wind loads. This paper presents the results of two post-occupancy monitoring campaigns, during the summer and winter seasons respectively, on a DSF building situated in Lisbon. The experimental data showed a close dependency of the air gap temperatures on incoming radiation and outdoor temperature and also on the type of shading device. These results can provide useful information for the design of DSF configuration and ventilation strategies to achieve an overall performance improvement under typical Portuguese weather conditions.